(untitled) (Research, Society and Development, 2020)
Objective: to understand the daily life of family members who care for children in a Pediatric Intensive Care Unit (PICU). Methodology: this is a study of qualitative descriptive exploratory approach with 10 family members of a PICU of a hospital located in the West region of Santa Catarina, which took place from July to September 2019. The data analysis was developed in accordance with the analysis of thematic content. Results: it was possible to identify two categories, which are entitled: spirituality as a force to overcome hospitalization and a new perspective of caring for oneself and the other. These, in turn, highlight the process that permeates the pre-existing experiences of life, the diagnostic revelation at the time of hospitalization and the process of resilience adopted by this family member to overcome adversity. Conclusion: the importance of the multiprofessional approach is evidenced, focused on a service that transcends the technological and the centrality in the patient, with emphasis on family members.